Ensuring the global COVID-19 vaccine equity: Universal vaccine access strategy in the context of low and-middle-income countries. Issue 4 (3rd April 2022) - Parray, Ateeb Ahmad; Yadav, Uday Narayan; Das, Anupom; Ali, ARM Mehrab; Mollick, Shemana; Saha, Senjuti; Mistry, Sabuj Kanti
ABSTRACT : Lockdowns and other COVID-19 containment measures enforced to kerb the pandemic have had a massive impact on the overall growth of the world. Income-generating activities have been reduced, but the impact is more consequential among the low- and middle-income countries. The disproportionate access to vaccines between wealthy and poor countries has resulted in 'vaccine apartheid.' An 'every-country-for-itself' approach or 'vaccine nationalism' coupled with 'vaccine hesitancy' has contributed to disproportionate access to and uptake of the COVID-19 vaccines. This paper argues that it is time for the decision-makers to adopt a Universal Vaccine Access Strategy (UVAS). The authors argue that sharing resources by establishing local production of vaccines wherever possible, timely donation of unused COVID-19 vaccines to developing countries and addressing vaccine hesitancy have become imperative to interrupt the emergence of new variants.